GOOD CORPORATE GOVERNANCE (GCG) DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI DETERMINASI NILAI PERUSAHAAN ( Studi Empiris pada Perusahaan perusahaan LQ45 yang terdaftar di Bursa Efek Indonesia periode 2017 – 2020) - Hj. Dewi Rejeki, SE., Ak., M.Si., CA.; Puput Winningsih (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This study aims to empirically prove the influence of Good Corporate Governance and Corporate Social Responsibility on firm value in LQ45 companies listed on the Indonesia Stock Exchange for the period 2017 to 2020 both partially and empirically, using several variables, namely Good Corporate Governance with 3 indicators. measurements such as Independent Board of Commissioners, Institutional Ownership, Managerial Ownership and Corporate Social Responsibility. The method used in this research is quantitative which according to the level of explanation includes associative research with a casual approach. The type of data used is secondary data with data sources from audited financial statements, namely LQ45 Companies Listed on the Indonesia Stock Exchange (IDX) based on time series for the period 2017 to 2019. The results of this study partially prove that Good Corporate Governance has no effect. on the value of the company, while Corporate Social Responsibility has an effect on the Firm Value of the Company, while simultaneously Good Corporate Governance and Corporate Social Responsibility have an effect on the Firm Value of the Company.